Let P(x) be a nonzero polynomial with integer coefficients. Let a0=0 and for i≥0 define ai+1=P(ai). Show that gcd for all m, n \in \mathbb{N}.
Problem
Source:
Tags: algebra, polynomial, induction, Recursive Sequences
26.03.2008 08:46
Induction after \max(m,n). In fact we can WLOG m>n, and we will do induction after m. Suppose m=1. Then the result is obvious \gcd(a_1,a_0) = a_1 = a_{\gcd(1,0)}. Suppose that we have proved for all pairs (m',n') such that m>m'>n'. Then \gcd(a_m,a_n) = \gcd(P^{(m-n)}(a_n),a_n) = \gcd(P^{(m-n)}(0),a_n)= \gcd(a_{m-n},a_n), which by induction is a_{\gcd(m-n,n)}, which obviously equals a_{\gcd(m,n)}.
28.02.2010 13:54
sorry, but who can explain for me why gcd(P^{(m - n)}(a_n);a_n) = gcd(P^{(m - n)}(0);a_n) (and I think that because a_0 = 0 so P^{(m - n)}(0) = 0) is it wrong thanks
27.03.2010 03:15
P^{m-n}(0) certainly need not equal 0. The reason is that a_n=a_n-0|P(a_n)-P(0)|P^{(2)}(a_n)-P^{(2)}(0)|\cdots|P^{(m-n)}(a_n)-P^{m-n}(0), so that if d|a_n and d|P^{(m-n)}(a_n) then d|P^{(m-n)}(0), and similarly, if d|a_n and d|P^{(m-n)}(0) then d|P^{(m-n)}(a_n).